2019
DOI: 10.24326/asphc.2019.5.4
|View full text |Cite
|
Sign up to set email alerts
|

ARBUSCULAR MYCORRHIZAL FUNGAL-ASSOCIATED BACTERIA AFFECT MYCORRHIZAL COLONIZATION, ESSENTIAL OIL AND PLANT GROWTH OF Murraya koenigii L.

Abstract: Murraya koenigii L. (family: Rutaceae) commonly called as curry leaf is a highly valued plant for aroma and medicinal value. The two dominant AM species Glomus mosseae and Acaulospora laevis were isolated from the rhizospheric soil of M. koenigii. A pot experiment was performed to see the interactive potential of G. mosseae and A. laevis alone or in combination with Pseudomonas fluorescens on M. koenigii. Various morphological and biochemical parameters were measured after 120 days. Overall results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bidondo et al (2011) indicated that bacteria can interact with root microbial community by mycorrhizosphere, inside spores or mycelia as observed in-vitro study. It was also reported that diazotrophic bacteria promoted AMF colonization and spores number that lead to higher acquisition of nutrients especially P and Zn with improved rhizospheric environment (Jangra et al 2019). Several strains of Azospirillum spp.…”
Section: Discussionmentioning
confidence: 97%
“…Bidondo et al (2011) indicated that bacteria can interact with root microbial community by mycorrhizosphere, inside spores or mycelia as observed in-vitro study. It was also reported that diazotrophic bacteria promoted AMF colonization and spores number that lead to higher acquisition of nutrients especially P and Zn with improved rhizospheric environment (Jangra et al 2019). Several strains of Azospirillum spp.…”
Section: Discussionmentioning
confidence: 97%